The epidemiology and incidence of dengue in Makkah, Saudi Arabia, during 2017-2019 - Melebari, Sami; Bakri, Rowaida; Hafiz, Abdul; Qabbani, Fadel; Khogeer, Asim; Alharthi, Ismail; Alhazmi, Sultan; Almalki, Yehya; Bulkhi, Rasha; Gammash, Razaz; Hakim, Ashwaq; Alkhyami, Ahmed; et al. (Saudi medical journal, 2021)
Objectives: To study the epidemiology of dengue incidence and understand the dynamics of dengue transmission in Makkah, Kingdom of Saudi Arabia (KSA), between 2017-2019. Methods: This is a cross-sectional study. Health and demographic data was obtained for all confirmed dengue cases in Makkah, KSA, in the years 2017-2019 from the Vector-Borne and Zoonotic Diseases Administration (VBZDA) in Makkah and the Makkah Regional Laboratory, KSA. In addition, entomological data about Aedes density was obtained from the VBZDA. Descriptive epidemiological methods were used to determine the occurrence and distribution of dengue cases. Results: Laboratory-confirmed dengue cases were higher in 2019 as compared to 2017 and 2018, suggesting an outbreak of dengue in Makkah, KSA, in 2019. The incidence of confirmed dengue cases was 204 in 2017, 163 in 2018 and 748 in 2019. Dengue mostly affected people in the 25-44 age group, accounting for approximately half of the annual dengue cases each year. Men were at a higher dengue incidence risk when compared to women, and Saudi women had a higher risk rate for dengue cases when compared to non-Saudi women in all 3 years studied. There was no dengue related death in these 3 years. Conclusion: The dengue incidence increased in Makkah, KSA, in 2019 as compared to the previous 2 years, owing to heavy rainfall in 2019. Post-rainfall Vector control efforts may help contain the disease in Makkah, KSA. Keywords: Dengue, incidence, Vector Borne diseases, Saudi Arabia [phrase omitted]